Electromagnetic interference shielding of graphene/PMMA composites depending on growth temperature of CVD-graphene - Kim, Seung Il; Kim, Jin Su; Moon, Ji Yun; Hyeong, Seok Ki; Ghods, Soheil; Choi, Jun Hui; Kim, Dasol; Park, Dong Seop; Heo, Keun; Lee, Jae Hyun (Synthetic Metals, 2023)
The research on graphene, driven by its exceptional mechanical, electrical, and thermal properties, has garnered significant attention, making it a promising multi-functional material for electronics. In this study, we investigated the effect of the synthesis temperature on the crystalline quality and the electromagnetic interference (EMI) shielding performance of graphene. We performed graphene synthesis on Cu foil at different temperatures (from 900° to 1050°C) and subsequently analyzed the samples using Raman spectroscopy. The results showed that the crystalline quality of graphene increased with increasing synthesis temperature. We then fabricated a 100-layer graphene/poly(methyl methacrylate) (PMMA) composite (GPC) and evaluated its electrical, mechanical properties, and EMI shielding effectiveness (SE). Our findings revealed the GPC with high crystalline graphene had a higher electrical conductivity and tensile strength than the GPC with defective graphene. In addition, the GPC with high crystalline graphene had a higher EMI SE, with a total SE of 14.16 dB, which is 140 % higher than that value for a defective graphene structure.
Keywords: Crystalline quality; CVD graphene; CVD synthesis; Electromagnetic interference shielding; Electromagnetic interference shielding effectiveness; Methacrylate composites; Multi-functional materials; Poly(methyl methacrylate); Poly-methyl methacrylates; Synthesis temperatures; Composite; Crystalline quality; CVD synthesis; EMI shielding; Graphene